Aplikasi Perlakuan Fisik untuk Mematahkan Dormansi terhadap Perkecambahan Benih dan Pertumbuhan Bibit Aren (Arenga pinnata Merr.) - Rahmaniah Rahmaniah; Muhammad Ermayn Erhaka; Tuti Heiriyani (Agroekotek View, 2018)
Palm trees are now getting scarce, as many are old and cut down. The absence of technology that can shorten the dormancy of sugar palm is an obstacle that is still faced in the provision of palm seeds. The cause of dormant seed dormancy is the thick skin of the seeds and the unbalanced stimulants and inhibitors present in spurring germination activity. Eliminating the dormancy period is one way for the provision of seeds briefly. This study used RAK method with one factor experiment. From the experiment there were 5 treatments with 5 replications. The treatment is a1: Without treatment (control), a2: Approximate to the bud eye, a3: Given a hole near the bud eye, a4: Beaten with a hammer on the seeds of palm sugar and a5: Soaked in water with an initial temperature of 75o C for 15 minutes. The results showed that the physical treatment to break the dormancy aren gives effect, on percentage parameter germination, sprout sprout 50% growth rate and length radikula. The hole treated treatment was the best treatment in declaring dormancy of palm seeds with the highest percentage of germination percentage of 66% and the fastest 50% sprout time growth rate of 0.64 (4.4 days)